Correlations Between Interleukin-11 Expression and Hypertensive Kidney Injury in a Rat Model of Renovascular Hypertension - Menendez-Castro, Carlos; Cordasic, Nada; Dambietz, Thomas; Veelken, Roland; Amann, Kerstin Ute; Hartner, Andrea; Hilgers, Karl Friedrich (American Journal of Hypertension, 2020)
BACKGROUND: Interleukin-11 (IL-11) is a pleiotropic cytokine of the interleukin-6 family. Recent studies revealed its crucial role in the development of cardiovascular fibrosis. In this study we examined IL-11 expression levels in the heart and the kidney exposed to high blood pressure in renovascular hypertensive rats and their correlations to fibrotic markers and kidney injury. METHODS: Two-kidney, one-clip renovascular hypertension (2K1C) was induced in rats. IL-11 expression was measured by real-time polymerase chain reaction in the left ventricle and the right kidney. The correlation of cardiac IL-11 expression with biomarkers of renal fibrosis was assessed. We further investigated IL-11 expression in 2K1C rats grouped into rats with malignant vs. nonmalignant hypertension (distinguishing criteria: weight loss, number of fibrinoid necrosis, and onion skin lesions). RESULTS: Thirty-five days after clipping, mean arterial pressure was significantly increased in 2K1C. Renal IL-11 expression was elevated in 2K1C. In the heart there was only a trend toward higher IL-11 expression in 2K1C. IL-11 in the kidney in 2K1C correlated with the expression of transforming growth factor (TGF)-β1/2, collagens, fibronectin, osteopontin, as well as tissue inhibitors of metalloprotease 1/2. There were also correlations of IL-11 with tissue collagen expansion, number of activated fibroblasts and serum creatinine, but no correlation with mean arterial pressure. Renal expression of IL-11 was highest in rats with malignant hypertension. CONCLUSIONS: Renal IL-11 expression of renovascular hypertensive rats is markedly increased and correlates with profibrotic markers and loss of function and might therefore serve as a biomarker for the severity of hypertensive nephrosclerosis.
CRIS-Team Scopus Importer:2020-04-14
Keywords: blood pressure; hypertension; interleukin-11 (IL-11); malignant hypertension; renal fibrosis; two-kidney one-clip renovascular hypertension (2K1C)